Fantastic plants and where to find them: niche occupancy analysis in neotropical epiphytic species - Lima, Keven dos Santos (2025)
Aim: Niche occupation and organism diversification are interrelated processes that shape biodiversity. This study investigates the relationship between niche occupation, phylogenetic relationships, and species distribution within the genus Microgramma (Polypodiaceae), a group of neotropical epiphytic ferns. Location: Neotropic. Taxon: Genus Microgramma (Polypodiaceae, ferns). Methods: We analyzed eight species from the Scaly clade, exploring patterns of co-occurrence and allopatry in relation to their environmental characteristics through species distribution modeling and predicted niche occupation profiles. Niche overlap was assessed based on the degree of environmental similarity and spatial co-occurrence. Results: Niche occupation varied significantly among phylogenetically close species, while niche overlap was greater among phylogenetically distant species. Broadly distributed species tended to co-occur, suggesting niche divergence that facilitates coexistence by occupying distinct niches within the same region. In contrast, allopatric species exhibited differentiation in their environmental niche occupation for specific variables. Despite being geographically separated, allopatric species demonstrated greater environmental similarity with each other than with broadly distributed species, indicating niche convergence. Main Conclusions: Environmental factors play a key role in shaping niche occupation strategies in Microgramma. Broadly distributed species show patterns of niche divergence to enable coexistence, while allopatric species exhibit niche convergence despite their geographical separation. These findings provide insights into co-occurrence dynamics and diversification in neotropical epiphytic ferns.